2021
DOI: 10.1097/gme.0000000000001738
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported sexual function of breast cancer survivors with genitourinary syndrome of menopause after fractional CO2 laser therapy

Abstract: Objective: The objective of this pilot study was to evaluate the change in sexual function following treatment with fractional CO2 laser therapy in breast cancer (BC) survivors with genitourinary syndrome of menopause (GSM). Methods: A single-arm feasibility study of BC survivors with symptoms of GSM, including dyspareunia and/or vaginal dryness, was conducted. Participants who received three treatments with fractional CO2 laser and 4-week follow-up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 43 publications
(109 reference statements)
3
52
0
Order By: Relevance
“…Our results are similar to those of a recent cohort study in BC women treated with CO 2 laser therapy, where FSFI score improved in the same magnitude, and with changes remaining 12 months after laser therapy [28]. Of note, three randomized studies [29][30][31] comparing laser therapy versus local hormonal therapy or a combination of both in postmenopausal women without breast cancer revealed that laser therapy and local hormonal therapy had similar efficacy on VVA symptoms, with improvement of FSFI scores in all of them.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those of a recent cohort study in BC women treated with CO 2 laser therapy, where FSFI score improved in the same magnitude, and with changes remaining 12 months after laser therapy [28]. Of note, three randomized studies [29][30][31] comparing laser therapy versus local hormonal therapy or a combination of both in postmenopausal women without breast cancer revealed that laser therapy and local hormonal therapy had similar efficacy on VVA symptoms, with improvement of FSFI scores in all of them.…”
Section: Discussionsupporting
confidence: 90%
“…This study protocol was amended to collect follow-up data at one and two years to augment the limited long-term data on this treatment. Patient-reported sexual function was collected at one-year and demonstrated improvement in the FSFI and FSDS-R scores [26]. Here, we report the two-year follow-up results.…”
Section: Introductionmentioning
confidence: 93%
“…Fractional CO 2 laser treatment has also been used in women with cancer, most commonly breast cancer. Data based on retrospective [21][22][23] and several small single-arm studies have shown improvement in vaginal symptoms and sexual function [24][25][26][27][28]. A major limitation of these studies has been a lack of long-term follow-up to evaluate persistence of benefit of this intervention.…”
Section: Introductionmentioning
confidence: 99%
“…42 Of the 64 participants, 59 women completed the study, and at the 4-week follow-up, all had an improvement in their sexual function scores measured by the Female Sexual Function Index and the Female Sexual Distress Scale Revised. 42 Thirty-nine women completed the 12-month follow-up and reported no adverse effects. 42…”
Section: Lidocainementioning
confidence: 99%
“…Finally, a pilot study that evaluated sexual function of breast cancer survivors with GSM symptoms enrolled 64 participants to receive 3 CO 2 laser treatments 42 . Of the 64 participants, 59 women completed the study, and at the 4‐week follow‐up, all had an improvement in their sexual function scores measured by the Female Sexual Function Index and the Female Sexual Distress Scale Revised 42 . Thirty‐nine women completed the 12‐month follow‐up and reported no adverse effects 42 …”
Section: Prescription Treatments For Genitorurinary Syndrome Of Menop...mentioning
confidence: 99%